CEO education and the ability to raise capital. (21st September 2020) - Gounopoulos, Dimitrios; Loukopoulos, Georgios; Loukopoulos, Panagiotis
Abstract: Research Question/Issue: Using a unique hand‐collected dataset, this study examines the role of chief executive officer (CEO) educational attainments in relation to newly public firms. Theoretical/Academic Implications: Using human capital, institutional and upper echelon theories, we hypothesize and demonstrate that CEO educational attainments do not unambiguously affect investors' perceptions of a firm's future prospects. Instead, their influence depends on the quality of CEO education as well as on the degree of uncertainty regarding the firm's future performance and the level of information asymmetry between issuers and prospective investors. To our knowledge, this is the first study that provides a comprehensive treatment of the role of CEO education in the IPO context. Research Findings/Insights: We find that initial public offering (IPO) firms led by CEOs with superior educational credentials—in terms of level and quality—are associated with lower levels of IPO underpricing. This association is mainly driven by CEOs that hold advanced degrees. Notably, a difference‐in‐differences approach based on two quasi‐natural experiments indicates that the impact of CEO education on IPO underpricing is more pronounced within environments characterized by lower information transparency. The baseline results also hold in the longer term, thereby confirming the value of signaling prestigious academic awards at the time of the IPO. Practitioner/Policy Implications: Our evidence on the importance of CEO education, and especially that CEOs with varying levels and quality of educational training might differentially affect newly listed firms, is useful to providers of financial capital and boards of directors interested in assessing the viability of new ventures. The implication of our study for IPO investors is that it is worth paying more to take an equity position in firms run by better educated CEOs.